Anthropometric characteristics according to the role performed by World Tour road cyclists for their team - Sánchez-Munoz, C.; Mateo-March, M.; Muros, J. J.; Javaloyes, A.; Zabala, M. (European Journal of Sport Science, 2022)
Certain anthropometric characteristics are required for athletes to successfully perform in elite endurance sports. The present study aims to analyse the anthropometric characteristics of professional cyclists according to their specialty. Anthropometric measurements were conducted of the body composition of 76 male professional road cyclists in line with International Society for Advancement of Kinanthropometry protocol. Fat mass did not differ (p > 0.05) between climbers, all-rounders and flat specialists, although the following anthropometric variables did differ according to the role played within the team (p < 0.05): Body mass (climbers: 63.8 ± 3.6, all-rounders: 68.8 ± 5.3, flat specialists: 74.5 ± 5.6 kg) skeletal body mass (climbers: 29.7 ± 1.6, all-rounders: 31.4 ± 1.9, flat specialists: 33.5 ± 2.4 kg); body surface area (climbers: 1.78 ± 0.07, all-rounders: 1.89 ± 0.10, flat specialists: 1.96 ± 0.1 m2); frontal area (climbers: 0.33 ± 0.01, all-rounders: 0.35 ± 0.02, flat specialists: 0.36 ± 0.02 m2). Anthropometric characteristics differ between world-class cyclists depending on their specialty. These differences could influence performance in relation to different types of road cycling competitions. The present study identified characteristics that could be used by coaches to evaluate their athletes in the context of elite or professional road cycling.